Translation of knowledge produced in a research group: a student reflection (Research, Society and Development, 2021)
The articulation of theory and practice is a growing need in nursing practice. It is in this context that the translation of knowledge needs to be considered in the training of this professional. Graduate research groups, for example, are a potential space for this initiative. Objective: To reflect on how the knowledge produced in a research group contributed to the training and professional qualification of nurses in light of the translation of knowledge. Method: This is a reflection article that portrays the experience of nursing graduate students who are members of a research group of a Nursing Graduate Program at the Federal University of Paraná. These experiences revolve around the knowledge produced through participation in the group and its contribution to professional training. Results: The experience of the group was represented by the categories: "Impact of the knowledge produced in the GPPGPS for the teaching/educating dimension of the nurse" and "Impact of the knowledge produced in the GPPGPS for the dimension of caring for the nurse". Subsequently, the knowledge produced in the research group was represented in the Model for the translation (or application) of knowledge, taking into account its stages. Final consideration: This reflection from the perspective of CT, allowed us to visualize how this knowledge produced in the research group had an impact through each stage of the action cycle. The research group is a space for academic discussion responsible for the emergence of results that can transform a professional practice with an impact on nursing practice on its various fronts, on health and society.